2014
DOI: 10.1016/j.genhosppsych.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of bipolar disorder in general primary care samples: a systematic review

Abstract: Objective To obtain an estimate of the prevalence of bipolar disorder in primary care. Methods We used the PRISMA method to conduct a systematic review in January 2013. We searched seven databases with a comprehensive list of search terms. Included articles had a sample size of 200 patients or more and assessed bipolar disorder using a structured clinical interview or bipolar screening questionnaire in random adult primary care patients. Risk of bias in each study was also assessed. Results We found 5595 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 36 publications
1
49
0
Order By: Relevance
“…Bipolar Disorder (BD) is a chronic and recurrent mental illness with a 3% to 5% lifetime prevalence (Cerimele et al, 2014, Merikangas et al, 2007) and is considered one of the leading causes of years of disability adjusted life years (DALYs) as well as years lived with a disability (YLDs) in young adults (Murray and Lopez, 1997). Alongside mood and cognitive deficits (Bora et al, 2009) BD is associated with a high incidence of medical conditions such as overweight/obesity, type 2 diabetes (T2D), cardiovascular disease (CVD), and stroke (Galvez et al, 2014, Mcintyre et al, 2005, McIntyre et al, 2004, Prieto et al, 2014, Sharma et al, 2014, Sylvia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Bipolar Disorder (BD) is a chronic and recurrent mental illness with a 3% to 5% lifetime prevalence (Cerimele et al, 2014, Merikangas et al, 2007) and is considered one of the leading causes of years of disability adjusted life years (DALYs) as well as years lived with a disability (YLDs) in young adults (Murray and Lopez, 1997). Alongside mood and cognitive deficits (Bora et al, 2009) BD is associated with a high incidence of medical conditions such as overweight/obesity, type 2 diabetes (T2D), cardiovascular disease (CVD), and stroke (Galvez et al, 2014, Mcintyre et al, 2005, McIntyre et al, 2004, Prieto et al, 2014, Sharma et al, 2014, Sylvia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, they also emphasized collaborative care’s strengths in managing bipolar disorder in a safety net population where the prevalence of bipolar disorder is higher than in other primary care settings (12). …”
Section: Resultsmentioning
confidence: 99%
“…However, dissemination of collaborative care into large health systems has revealed that clinicians working in collaborative care often face diagnosing and treating other more severe and complex psychiatric illnesses including bipolar disorder (11). Despite research showing that bipolar spectrum illnesses may occur in up to 10% of primary care patients in some primary care settings (12), and that the prevalence of bipolar disorder in primary care is approximately twice the prevalence in the general population (1214), few studies are available to guide collaborative care consultation by psychiatrists in helping to improve the diagnosis and treatment of bipolar disorder in primary care. Moreover, despite the high prevalence, primary care clinicians are generally less comfortable with diagnosing and treating bipolar disorder compared to major depressive disorder and anxiety disorders, and view patients with bipolar disorder as complex (15).…”
Section: Introductionmentioning
confidence: 99%
“…In primary care settings the MDQ commonly results in false positives, meaning that many individuals who screen as positive do not have bipolar disorder on the basis of structured interview or clinical examination (9, 19). This is due to the lower prevalence of bipolar disorder in primary care in comparison with specialty care settings in which the MDQ was initially studied and validated (20).…”
Section: Diagnosis In Primary Carementioning
confidence: 99%
“…The prevalence of bipolar disorder in primary care settings is approximately twice the prevalence in the general population (7, 9). Treatment seeking by patients with bipolar disorder is divided about equally between primary care and specialty mental health settings (7, 10).…”
mentioning
confidence: 99%